ACE and ACE2 in Inflammation: A Tale of Two Enzymes - Reddy Gaddam, Ravinder; Chambers, Stephen; Bhatia, Madhav (Inflammation & Allergy-Drug Targets (Discontinued), 2014)
The renin-angiotensin system (RAS) conceived as a coordinated hormonal cascade plays an important role in controlling multiple functions in many organs and is much more complex than previously thought. The RAS has continued to expand, with the identification of new components, functions and subsystems. Angiotensin-converting enzyme (ACE) and its novel homolog angiotensin converting enzyme 2 (ACE2) are two key enzymes involved in the synthesis of bioactive components of the RAS. The main active peptides of the RAS include angiotensin II (Ang II), Ang III, Ang IV, and angiotensin-(1-7) [Ang-(1-7)] among which Ang II and Ang-(1-7) are much more important in health and disease. The axis formed by ACE2 represents an endogenous counter-regulatory pathway within the RAS, and its actions are opposite to those of the ACE axis. Conventionally the RAS has been considered to be important in the cardiovascular system, metabolism, cell growth and homeostasis. In recent years, a key role of ACE and ACE2 and their peptides has been recognized in the inflammatory process in conditions such as cardiac hypertrophy, pulmonary hypertension, glomerulonephritis, lung injury, sepsis, and acute pancreatitis. Investigations are ongoing to better understand the role of the RAS in inflammation. A comprehensive understanding of the RAS components in inflammation can provide new possibilities for therapeutic approaches against inflammatory diseases. In this review, we discuss our current understanding of the subject, based on recent findings, on the role of ACE and ACE2 in inflammation.
Keywords: angiotensin-converting enzyme 2